Optimization of TIG welding parameters for enhanced mechanical properties of Al 7075 weldments - Yahaya, Madaniyyu Sulaiman; Kumar, Dinesh; Auwal, Shamsu Tukur; Mokoyo, Mahdi; Gambo, Abdulhaq Saleh; Umar, Tijjani Aminu; Tijjani, Abubakar (Kathmandu University Journal of Science Engineering and Technology, 2024)
Al 7075 alloy is widely used in aerospace, automotive, and other high-performance industries due to its excellent strength-to-weight ratio and mechanical properties. However, its weldability, particularly using Tungsten Inert Gas (TIG) welding, presents significant challenges, including softening of the weld zone, solidification cracking, and the formation of defects in the heat-affected zone (HAZ). These challenges degrade mechanical properties such as tensile strength, hardness, and ductility, limiting the use of Al 7075 in critical welded applications. This study investigates the optimization of TIG welding parameters to improve the mechanical performance of Al 7075 weldments. A systematic experimental approach was employed, where key TIG welding parameters, including current (ranging from 120A to 180A), gas flow rate, and heat input, were varied to assess their effects on weld quality. Two plate thicknesses, 6mm, and 16mm, were utilized to explore the influence of material thickness on mechanical properties. Mechanical testing, including hardness, and tensile strength, was performed to quantify the impact of welding parameters. The findings demonstrate that the welding current has a significant effect on the mechanical properties of Al 7075 weldments. For both the 6mm and 16mm thick plates, moderate welding currents, particularly around 150A to 160A, resulted in the best overall mechanical performance. The 6mm plate exhibited a peak tensile strength of 325 MPa at 160A, with minimal hardness reduction in the weld center (18%), weld zone (28%), and HAZ (9.5%). The 16mm plate demonstrated a peak tensile strength of 290 MPa at 160A, with hardness reductions of 25%, 22.2%, and 9% in the weld center, weld zone, and HAZ, respectively. Excessively high currents (170A to 180A) resulted in increased hardness reduction and reduced tensile strength due to overheating and excessive thermal softening. Overall, 160A was found to be the optimal welding current for both plate thicknesses, balancing heat input, and weld quality.